Ecological Status of the Herpeto-Mammalian Fauna of the Padma River and its Adjacent Areas, Rajshahi and their Conservation Issues (Bangladesh Journal of Zoology, 2012)
Status and diversity of animals are the important indicators for a  healthy habitat of animals. We conducted a survey on ecology and status of  herpeto-mammalian fauna from November 1995 to October 1996 in the Padma river and its adjacent areas, Rajshahi. To achieve the objectives direct field observation and interviewing local people were made by employing standard  methods. A total of 50 species of herpeto-mammalian fauna was recorded from the  study area. Of these, 5(10%) were amphibians, 20 (40%) reptiles and 25 (50%) mammals. In the amphibians, 3 species were common, rest one species was fairly  common and one few. In the reptiles, 5 species were very common, 4 common, 7 fairly common, 3 few and only one species was occasionally found. Of the mammals, 2 species were very common, 5 common, 10 fairly common, 6 few and 2 species were occasional. Among the total species, 3 species of amphibians were vulnerable nationally, 4 species of reptiles were critically endangered, 4 endangered and 4 vulnerable and one species of mammals were critically endangered (Lutra lutra), 6 endangered and 4 species were vulnerable nationally. Group discussion with the local people indicated that species diversity of herpetomammalian fauna has been decreased day by day in the study area. This might be due to the results of highly disturbance by human. Meanwhile, increase of human  population, destruction of habitat, expansion of agricultural activities, illegal hunting and trade are the main causes for declining herpeto-mammalian fauna in  the study area. The study suggests that creation of public awareness, improvement of ecological condition and implementing a management action plan are necessary to conserve the herpeto-mammalian fauna in the study area DOI: http://dx.doi.org/10.3329/bjz.v40i1.12903 Bangladesh J. Zool. 40(1): 135-145, 2012